End-User Development of Voice User Interfaces based on Web content - Ripa, Gonzalo (2019)
Voice Assistants, and particularly the latest gadgets called smart speakers, allow end users to interact with applications by means of voice commands. As usual, end users are able to install applications (also called skills) that are available in repositories and fulfill multiple purposes. In this work we present an end-user environment to define skills for voice assistants based on the extraction of Web content and their organization into different voice navigation patterns. We describe the approach, the end-user development environment, and finally we present some case studies based on Alexa and Amazon Echo.